Sistem Pendukung Keputusan Menentukan Jenis Pestisida Nabati Untuk Hama Tanaman Kakao Menggunakan Metode Simple Additive Weighting (SAW) - Ronal Taruk Padang; Mirfan, Mirfan; Guntur, Guntur; Mila Jumarlis (Prosiding SISFOTEK, 2023)
Plantation is an activity of utilizing resources carried out by humans to pruduce food, industrial raw materials, or energy sources as well as to manage their environment, including in Tana Toraja Cocoa isone of the leading commodity crops in Toraja land because this plant has an important role as a source of economic develotment and a source of income for Tana Toraja famers. Based on the conditions at the research site, so far farmers are still not precise in using and determining the types of botanical pesticides for pests on cocoa plants. Therefore, a decision support system was designed using the SAW method, in order to make it easier for farmers to make decisions about vegetable pesticides to be used. The results of this study are designing a decision support system to determine the type of botanical pesticide to eradicate pests on cocoa plants based on a website. After going through the SAW algorithm calculations, the results obtained are the best alternative after ranking, the highest value for each alternative is the best vegetable pesticide according to the pest. Who attacked.